Armed Conflict and Environment From World War II to Contemporary Asymmetric Warfare - Briesen, Detlef (Nomos Verlagsgesellschaft mbH & Co. KG, 2018)
This study is the first to analyse the manifold interrelations between armed conflicts and the human and natural environments both historically and sociologically. While most research to date has dealt with this topic primarily with regard to environmental destruction caused by acts of war or armament in peacetime, this publication goes one step further by highlighting the historical changes to this complex interrelationship with concrete examples: from the Second World War in Europe and Asia via the classic proxy war in Vietnam to the current asymmetric wars in South Asia. At the same time, it focuses on systematic questions: How do environments influence armed conflicts? How do wars change environments? And how do complete 'war landscapes' (warscapes) emerge, in which war and militarisation permanently change the relations between people and their environment? With contributions by: Detlef Briesen, Anthony Goreau-Ponceaud, David Pickus, Sarada Prasanna Das, Nguyen Thi Hanh, Nguyen Thi Thuy Hang, Dao Duc Thuan/Nguyen Van Ngoc, Tim Kaiser, Dam Thi Phuong Thuy/Nguyen Van Bac, Brigitte Sébastia, Manish Tiwari, Babu Rangaiah/Kumaresan Raja, Martin Dinges.